The mitigation effect of free ammonia and free nitrous acid on nitrous oxide production from the full-nitrification and partial-nitritation systems. (March 2023) - Peng, Lai; Qiu, Huiling; Li, Shengjun; Xu, Yifeng; Liang, Chuanzhou; Wang, Ning; Liu, Yiwen; Ni, Bing-Jie
Graphical abstract: Highlights: Short-term FA and FNA treatment on FN sludge instantly reduce N2 O at all DO levels. The dependency of N2 OR on DO was altered by exposing FN sludge to high FNA. Short-term exposure of PN sludge to high FNA abolished N2 O production. FNA treatment on sludge led to 3.5% more cost, while FA treatment saved 2% cost. Abstract: The potentials of using endogenous free ammonia (FA) and free nitrous acid (FNA) as nitrous oxide (N2 O) mitigators were investigated in treatment of both mainstream and sidestream wastewater. Although the N2 O emission factor of a sidestream partial-nitritation (PN) reactor (averaged 1.70 % ± 0.39 %, n = 30) was about 2.4 times higher than a mainstream full-nitrification (FN) reactor (averaged 0.72 % ± 0.24 %, n = 30) (P < 0.01), one-hour exposure of PN sludge to 1.5 mg HNO2 -N/L FNA could virtually abolish N2 O emission. As for FN sludge, both 45 mg NH3 -N/L FA and 0.015 mg HNO2 -N/L FNA successfully mitigated N2 O production at varying dissolved oxygen (DO) levels (50 % vs 61 %), while 1.5 mg HNO2 -N/L FNA not only reduced more N2 O (92 %) but also altered the N2 O dependency on DO. Both FNA and FA sludge treatment were effective N2 O mitigation strategies with FNA toward the end of carbon neutrality and FA being more economically appealing (2 % cost saving).